"Green Oncology": The Italian Medical Oncologists' Challenge to Reduce the Ecological Impact of their Clinical Activity. Issue 3 (May 2014) - Bretti, Sergio; Porcile, Gianfranco; Romizi, Roberto; Palazzo, Salvatore; Oliani, Cristina; Crispino, Sergio; Labianca, Roberto
For decades Western medicine has followed a biomedical model based on linear thinking and an individualized, disease-oriented doctor-patient relationship. Today this framework must be replaced by a biopsychosocial model based on complexity theory and a person-oriented medical team-patient relationship, taking into account the psychological and social determinants of health and disease. However, the new model is already proving no longer adequate or appropriate, and current events are urging us to develop an ecological model in which the medical team takes into account both individual illness and population health as a whole, since we are all part of the biosphere. In recent years, the rising costs of cancer treatment have raised a serious issue of economic sustainability. As the population of our planet, we now need to rapidly address this issue, and everyone of us must try to reduce their ecological footprint, measured as CO2 production. Medical oncologists need to reduce the ecological footprint of their professional activity by lowering the consumption of economic resources and avoiding environmental damage as much as possible. This new paradigm is endorsed by the Italian College of Hospital Medical Oncology Directors (CIPOMO). A working group of this organization has drafted the "Green Oncology Position Paper": a proposal of Italian medical oncology (in accordance with international guidelines) that oncologists, while aiming for the same end results, make a commitment toward the more appropriate management of health care and the careful use of resources in order to protect the environment and the ecosphere during the daily exercise of their professional activities.